Nanostructured ceramic oxides for supercapacitor applications - Balakrishnan, Avinash; Subramanian, K. R. V. (CRC Press, 2014)
"In order to develop a high performance supercapacitor, it is generally desirable to design the geometry and morphology of supercapacitor electrode with fully utilized surface area and well defined pore structures, which can lead to faster ion movement contacting the electroactive materials and promote faradic redox reactions. In short, the present book proposes preparation methodology of various one dimensional metal oxide nanostructures used as electrode overlays and methods by which the conductivity of the stochiometric metal oxide can be increased"--